Socioeconomic status and left ventricular ejection fraction decline in breast cancer survivors following receipt of doxorubicin (PREVENT WF-98213) - Arnethea L. Sutton; Nathaniel S. O’Connell; Alexander R. Lucas; Kristine C. Olson; Kerryn W. Reding; Vanessa B. Sheppard; Bonnie Ky; Kathryn J. Ruddy; Kathryn E. Weaver; W. Gregory Hundley (Cardio-Oncology)
Abstract Cancer survivors receiving doxorubicin may experience left ventricular ejection fraction (LVEF) decline during and following treatment; however, explanations for variations in decline beyond dosage differences, such as those related to socioeconomic status (SES), have not been fully examined. We conducted a retrospective analysis of a cohort of 215 breast cancer survivors receiving doxorubicin. SES factors (e.g., household income, education) were collected via a survey at a baseline and EF was assessed using magnetic resonance imaging. Linear regression models showed that prior to treatment, no SES factors were associated with LVEF. However, six months following treatment, survivors who were unemployed for reasons other than retirement and disability experienced greater LVEF declines compared to survivors who were employed ((b = 2.79 [95% confidence interval (CI): 0.37–5.20; p = 0.026). Our study demonstrated that non-clinical factors associated with social drivers of health, such as socioeconomic status, contribute to subclinical cardiovascular dysfunction and therefore supports further investigation of mechanisms behind these associations. Trial registration NCT01988571 (WF-98213).